Determinants of liquidity riskin the countries of the European economic area - Agnieszka Wysocka (Journal of Banking and Financial Economics (JBFE), 2023)
The paper documents cross-country variation in the relationship between the deposit insurance scheme and liquidity risk in banks and explores the banking sector specific and macroeconomic determinants that can explain the variation. There is a lack of articles exploring the phenomenon in Europe, authors studying the issue focus on the United States and other parts of the world, so it is difficult to apply their results to Europe. The results of their research are also ambiguous. Using data from 28 countries of the European Economic Area by means of panel regression calculated with the use of GLS estimator with random effects, I established that an increase in deposit insurance coverage reduces the risk of liquidity. The study provides new information to help evaluate deposit insurance schemes across EEA countries.
Keywords: G01; G21; G22; G28; 330; Financial Institution; Liquidity Risk; Deposit Insurance